2001
DOI: 10.17221/7894-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E and vitamin A supplementation on performance, thyroid status and serum concentrations of some metabolites and minerals in broilers reared under heat stress (32 degrees C)

Abstract: An experiment on Cobb-500 male broilers was conducted to evaluate the effects of vitamin E (α-tocopherolacetate), vitamin A (retinol), and their combination on broiler performance and serum concentrations of triiodothyronine (T 3 ), thyroxine (T 4 ), adrenocorticotropine hormone (ACTH) and some metabolite and mineral concentrations in broilers reared under heat stress (32°C). One day-old 120 broilers were randomly assigned to 4 treatment groups, 3 replications of 10 birds each. The birds were fed either a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
22
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 36 publications
9
22
0
4
Order By: Relevance
“…Previous studies in different animal species revealed a protective role of vitamin E under various stress conditions (Brzezińska-Slebodzińska 2001; Sahin et al, 2001;Sarandöl et al, 2005). Most notably, in lead induced thyroid dysfunction in mice administration of vitamin E has been shown to maintain ID-I activity and in Se and vitamin E deficient rats vitamin E administration increased hepatic ID-I activity (Yue et al 1998).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies in different animal species revealed a protective role of vitamin E under various stress conditions (Brzezińska-Slebodzińska 2001; Sahin et al, 2001;Sarandöl et al, 2005). Most notably, in lead induced thyroid dysfunction in mice administration of vitamin E has been shown to maintain ID-I activity and in Se and vitamin E deficient rats vitamin E administration increased hepatic ID-I activity (Yue et al 1998).…”
Section: Discussionmentioning
confidence: 98%
“…These negative effects are found to be greater in poultry with a high potential for growth rate (Cahaner et al 1998;Settar et al 1999). High thermal loads may depress enterocyte proliferation, reduction in villus mass and dry weight per unit length of jejunum (Sahin et al 2001). A number of morphologic and physiologic changes occur in the gastrointestinal tracts of chickens exposed to heat stress.…”
Section: Feed Intake and Nutrient Utilizationmentioning
confidence: 99%
“…Sedangkan pada ayam yang dipelihara pada suhu 32 0 C pemberian antioksidan sari buah mengkudu 1.000 ppm dapat memberikan hasil yang sama dengan kadar tiroksin pada ayam broiler yang dipelihara pada temperatur netral. Aktivitas kalenjar tiroid dipengaruhi oleh kondisi lingkungan, pada ayam yang mengalami cekaman panas aktivitas kelenjar tiroid mengalami penurunan (Sahin et al, 2001;Gyorffy et al, 2009) dan akan mempengaruhi sekresi hormon yang dihasilkannya.…”
Section: Pengaruh Perlakuan Terhadap Kadarunclassified
“…Kadar hormon tiroksin pada ayam yang dipelihara pada suhu 20 0 C yaitu 0,916 µg/dl lebih tinggi dibandingkan dengan ayam yang dipelihara pada suhu 26 dan 32 0 C yaitu 0,596 µg/dl dan 0,366 µg/dl. Hal ini sesuai dengan penyataan Sahin et al (2001) terjadi penurunan konsentrasi hormon T3 (Triiodotironin) dalam sirkulasi darah. Lebih lanjut Decuypere et al (2005) dan Downing dan Bryden, (2002) menyatakan bahwa hormon tiroksin dihasilkan oleh kelenjar tiroid dan Ringer (1976) menyatakan terdapat hubungan antara musim dengan aktivitas kelenjar tiroid, pada musim panas aktivitas kelenjar tiroid rendah dibanding pada musim dingin.…”
Section: Pengaruh Perlakuan Terhadap Kadarunclassified
See 1 more Smart Citation